Learned by heart - Donoghue, Emma 1969- (Little, Brown and Company, 2023)
"A heartbreakingly gorgeous novel based on the true story of two girls who fall secretly, deeply, and dangerously in love at boarding school in 19th century York, from the bestselling author of Room and The Wonder. Drawing on years of investigation and Anne Lister's five-million-word secret journal, Learned by Heart is the long-buried love story of Eliza Raine, an orphan heiress banished from India to England at age six, and Anne Lister, a brilliant, troublesome tomboy, who meet at the Manor School for young ladies in York in 1805 when they are both fourteen. Emotionally intense, psychologically compelling, and deeply researched, Learned by Heart is an extraordinary work of fiction by one of the world's greatest storytellers. Full of passion and heartbreak, the tangled lives of Anne Lister and Eliza Raine form a love story for the ages"--
Keywords: Lister, Anne / 1791-1840 / Fiction; Raine, Eliza / 1791-1860 / Fiction; Boarding schools / Fiction; Girls' schools / Fiction; Interpersonal relations / Fiction; Lesbian teenagers / Fiction; Racially mixed people / Fiction; First loves / Fiction; York (England) / Social life and customs / 19th century / Fiction; Lesbians / Fiction; Mental illness / Fiction; York (England) / History / 19th century / Fiction; Internats / Romans, nouvelles, etc; Écoles de filles / Romans, nouvelles, etc; Adolescentes lesbiennes / Romans, nouvelles, etc; Premier amour / Romans, nouvelles, etc; Lesbiennes / Romans, nouvelles, etc; Maladies mentales / Romans, nouvelles, etc; FICTION / LGBTQ+ / General; Lister, Anne / 1791-1840; Raine, Eliza / 1791-1860; Bildungsromans; Boarding schools; Interpersonal relations; Lesbian teenagers; Lesbians; Manners and customs; Mental illness; Racially mixed people; England / York; LGBTQ+ people / Fiction; Private schools / Fiction; 1800-1899; Historical fiction; Romance fiction; Biographical fiction; Fiction; History; Lesbian fiction; Novels; Queer fiction; School fiction; LGBTQ+ fiction